Xanthogranulomatous prostatitis with benign prostatic hyperplasia: A rare combination - Navjot Grewal; Amit Tuli; Francis K Sridhar; Kim John Mammen (Wolters Kluwer Medknow Publications, 2017)
Xanthogranulomatous prostatitis is a rare benign granulomatous inflammation of the prostate. Only ten cases of such pathology have been reported in literature. Patients usually present with symptoms of lower urinary tract symptoms. It occasionally resembles other prostatic diseases such as prostatic carcinoma and abscess. Imaging techniques are not useful in the diagnosis of xanthogranulomatous prostatitis; hence, it is diagnosed only on the basis of histopathological examination of prostate.